Comparison of the effectiveness of home visits and telephone follow-up on the self-efficacy of patients having undergone coronary artery bypass graft surgery (CABG) and the burden of their family caregivers: A randomized controlled trial - Gohari, Foruzan; Hasanvand, Shirin; Gholami, Mohammad; Heydari, Heshmatolah; Baharvand, Parastoo; Almasian, Mohammad (Investigación y Educación en Enfermería, 2023)
Objective. This study aimed to compare home visits and telephone follow-up effectiveness on patients' self-efficacy undergoing Coronary Artery Bypass Graft Surgery –CABG- and caregivers’ burden. Methods. In this randomized clinical trial, 114 patients undergoing CABG were assigned to the three groups of home visits, telephone follow-up, and control based on the stratified block randomization. The self-management program of the home visit group included four face-to-face 60-minute training sessions once a week, and for the telephone follow-up group, four 30-minute telephone counseling sessions twice each week for a month. The control group received routine care. Data were collected using the cardiac rehabilitation self-efficacy questionnaire and the caregiver burden scale before and after the intervention. Results. Before the study, there were no statistically significant differences between the three groups in terms of the means of self-efficacy and caregiver burden scores. However, there was a statistically significant difference between the home visit and control groups (p<0.001) and between the telephone follow-up and control groups (p<0.001) after the intervention, with increased self-efficacy and reduced caregiver burden reported. In contrast, there was no significant difference between the home visit and telephone follow-up groups regarding self-efficacy and caregiver burden scores. Conclusion. Both methods of self-management education have similar effectiveness in increasing self-efficacy and reducing the caregiver burden after discharge for patients who have undergone CABG.